2014
DOI: 10.1063/1.4862063
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of graphene devices before and after transfer to different substrates

Abstract: The entire graphene field-effect-transistor (FET) devices first fabricated on SiO2/Si are peeled from the surface and placed on a different wafer. Both longitudinal and transverse resistivity measurements of the devices before and after the transfer are measured to calculate the mobility for a direct comparison. After transferred to different SiO2/Si wafers, the mobility generally is comparable and the defect density does not show any significant increase, which indicates the degradation due to the transfer pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…18 PMMA residues probably remain during the transfer process on the as-transferred graphene surface, leading to degradation of the device performance. 19 High temperature annealing under different atmospheres (including N 2 , H 2 , H 2 / Ar, and vacuum) is one of the effective ways to clean PMMA from the graphene surface and improve the electrical performance to that of ideal graphene. [20][21][22] Hong et al reported that PMMA membrane with Pd nanoparticles on graphene shows high response and good selectivity to hydrogen because the Pd nanoparticles enhance the sensor response and the PMMA membrane blocks gas molecules with higher molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…18 PMMA residues probably remain during the transfer process on the as-transferred graphene surface, leading to degradation of the device performance. 19 High temperature annealing under different atmospheres (including N 2 , H 2 , H 2 / Ar, and vacuum) is one of the effective ways to clean PMMA from the graphene surface and improve the electrical performance to that of ideal graphene. [20][21][22] Hong et al reported that PMMA membrane with Pd nanoparticles on graphene shows high response and good selectivity to hydrogen because the Pd nanoparticles enhance the sensor response and the PMMA membrane blocks gas molecules with higher molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…We use a 20 -30 nm thick h-BN layer via a micromechanical transfer process 16 to cover the entire graphene region, which simultaneously protects graphene from chemical solvent or resist contaminations and serves as an effective top gate dielectric layer. After top gate electrodes are fabricated and tested, we transfer the entire functional graphene/h-BN devices from Si/SiO 2 substrates to YIG utilizing a previously developed transfer technique 6,17 . The optical images of graphene/h-BN devices before and after transfer are illustrated in Fig.…”
mentioning
confidence: 99%
“…Finally, the PMMA is dissolved with acetone followed by careful rinsing and drying, and the device is ready for electrical transport and/or Raman measurements. This technique was previously applied to fabricate graphene devices on SrTiO 3 , a high nominal dielectric constant pervoskite material [5,6]. The transfer steps are schematically shown in Fig.…”
mentioning
confidence: 99%
“…To bring graphene in contact with YIG substrates, we apply a previously developed transfer technique (see SM) that is capable of transferring pre-fabricated functional graphene devices to any target substrates [5]. We first fabricate exfoliated single-layer graphene devices on 290 nm-thick SiO 2 atop highly doped Si substrates using standard electron-beam lithography and Au electron-beam evaporation.…”
mentioning
confidence: 99%